Development of management policy for the marine ornamental fish and invertebrate fishery in Puerto Rico: A case study - Hardin, M. P.; LeGore, R. S. (Revista de Biología Tropical, 2005)
In recent years the collection of tropical marine organisms for the aquarium trade has become perceived as an activity with an unsustainable history as well as obvious potential for rehabilitation through resource-based fisheries management and consumer-oriented product certification. In the case of Puerto Rico, collection of ornamentals has existed for decades, though unregulated due to a weak fisheries law dating from the 1930’s. The new Fisheries Law 278 of 1998 enabled new regulatory approaches for marine ornamentals, which were met with serious challenges rooted in (1) an information gap concerning the fishery regarding participant numbers, collection methods and export volumes, and (2) the absence of consultation of fishers by agency regulators. The information gap led to worst-case assumptions of impact by regulators, and a closure of the fishery, which set the stage for threatening personal confrontations and lawsuits, the latter leading to de facto resource management by judicial order. To redress these issues and move management back into the arena of science and public policy, regulators have initiated a three-phase program: (1) characterize fisher numbers, methods and exports, (2) describe populations and biology of commercial species, and (3) propose appropriate fisheries management approaches. This paper describes only the first phase of this program.